The Relationship between Occupational Stress and Mental Health in Central Bafgh Iron Workers - Faezeh AFKHAMI AGHDA; Mohammad AFKHAMI AGHDA; Maryam FALAHATI; Hossein MOAHAMMAD MIRZAEE (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: Occupational stress is one of the most important phenomena in the workplace. Mental health, as an important factor in all personal, social, and occupational life aspects, is one of the areas of interest in mental health. The purpose of this study was to determine the relationship between job stress and mental health among workers of central iron ore in Bafgh City, Iran. Methods: This was a descriptive correlational study. The statistical population included 2400 people (1600 workers and 800 employees) working in central Bafgh iron ore in 2014. The sample size was estimated as 331 using the Morgan and Krejcie table. Approximately, 216 persons were employed in the labor sector and 115 in the employment sector. Data collection tools included the Goldberg general health questionnaire (GHQ) and Depression Anxiety Stress Scales (DASS). The DASS was designed in three parts. The first part included demographic data (7 items). The second section had 28 questions and dealt with the participants' general health status. The third part included 42 questions and was about occupational stress. Later, Spss21 was used and Pearson correlation coefficient and regression tests were run to analyze the data and test the hypotheses. Results: The results showed that mental health was higher in employees, while job stress was higher among the workers. This indicated a significant association between job stress and mental health in both employees and workers. However, regarding the demographic variables, only gender was related to mental health and rest of the demographic variables had no significant relationship with mental health and job stress (5≥participants). Conclusion: Occupational stress was related to mental health in employees and workers; this can affect the level of production and product quality. Furthermore, occupational tress and mental health not only affect the workers and employees, but also expose the society and other people at risk.  Consequently, it is necessary to plan and render different services at the occupation environment to decrease job stress and improve the current situation.